A case of pityriasis rubra pilaris secondary to ponatinib - Ariana Nateghi; Florence Lagacé-Thomassin; Julie Desrochers (SAGE Open Medical Case Reports)
Ponatinib, a tyrosine kinase inhibitor used for chronic myeloid leukemia and acute lymphoblastic leukemia, can cause rare cutaneous side effects. In this case, a 63-year-old woman developed a pityriasis rubra pilaris-like eruption 1 month after starting the drug. The skin reaction improved with dose reduction and recurred more mildly at a lower dose. Symptomatic relief was achieved with topical tretinoin, triamcinolone, and emollients. This case underscores the importance of managing dose-dependent skin reactions while maintaining cancer therapy.